2015
DOI: 10.1016/j.bbrc.2015.06.067
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin improves cardiac function through regulation of energy metabolism in Streptozotocin-Nicotinamide induced diabetic mice after myocardial infarction

Abstract: It is well recognized that the incidence of heart failure and the risk of death is high in diabetic patients after myocardial infarction (MI). Accumulating evidence showed that puerarin (PUE) has protecting function on both cardiovascular disease and diabetes. The aim of this study is to explore whether puerarin could improve cardiac function in diabetic mice after MI and the underlying mechanism. The left anterior of Streptozotocin (STZ)-Nicotinamide (NA) induced diabetic mice were ligated permanently except … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Besides this cellular model of arrhythmia, several studies had announced puerarin could accelerate cardiac angiogenesis and improve cardiac function of myocardial infarction rats by upregulating VEGFA, Ang-1 and Ang-2 33 . Another study demonstrated that puerarin improved cardiac function after MI in diabetic mice through increasing the expression and translocation of GLU4 while attenuating the expression and translocation of CD36 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides this cellular model of arrhythmia, several studies had announced puerarin could accelerate cardiac angiogenesis and improve cardiac function of myocardial infarction rats by upregulating VEGFA, Ang-1 and Ang-2 33 . Another study demonstrated that puerarin improved cardiac function after MI in diabetic mice through increasing the expression and translocation of GLU4 while attenuating the expression and translocation of CD36 34 .…”
Section: Discussionmentioning
confidence: 99%
“…NA in saline (120 mg/kg) was injected i.p. 15 min prior to the administration of STZ (22). The weight of each mouse and the concentration of glucose in the blood were measured to ensure that the diabetic mouse model was properly established.…”
Section: Cells and Reagents The Ct26 Cell Line Was Provided Bymentioning
confidence: 99%
“…Among flavonoids, puerarin is one of the most bioactive compounds and exhibits many pharmacological effects including antioxidant, anti-inflammation, vasodilation, and improvement of endothelial function through different mechanisms of actions [11]. Accumulating studies found that puerarin may inhibit cardiac fibrosis and accelerate cardiac angiogenesis to improve cardiac function in MI animals [12,13,14]. Due to the low solubility and poor bioavailability of puerarin, several modified crystal forms of puerarin were developed by Beijing Key Laboratory of Polymorphic Drugs of the Institute of Materia Medica of the Academy of Medical Sciences.…”
Section: Introductionmentioning
confidence: 99%